High-elasticity crease-resistant fabric and preparation method thereof
By introducing chemical bonds between benzene rings and hard chain segments into spandex fabrics and filling fiber pores with finishing agents, the problem of elastic properties of spandex fabrics due to pores during the production process is solved, and high elasticity and wrinkle-proof fabric preparation is achieved .
Patent Information
- Application Number
- CN202411574510.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-11-06
AI Technical Summary
The gas or solvent introduced by spandex fabrics during the production process leads to pores in the fibers, affecting density and continuity, causing the fibers to be easily broken or deformed, and weakening the elastic properties.
By introducing the benzene ring to form stable chemical bonds with the urea functional groups of the hard segment after polyurethane polymerization, the tightness of the hard segment is improved, and the fiber pores are filled with finishing agents to increase the fiber thickness and wrinkle resistance.
Effectively hinder the sliding and relative displacement of the hard segment of the fiber, improve the elasticity and wrinkle resistance of the fabric, and enhance the denseness and continuity of the fiber.
Smart Images

Figure BDA0005121437280000081 
Figure BDA0005121437280000091
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of textile fabric preparation, and particularly relates to a highly elastic and wrinkle-resistant fabric and a preparation method thereof. Background Art
[0002] Spandex is an elastic fiber fabric mainly composed of polyurethane, with a network structure formed by a block copolymer composed of soft segments and hard segments, which gives it excellent elasticity and good hygroscopicity. The fabric made of spandex gives the user a cool and comfortable feeling. Although spandex fabric has good elasticity, the gas or solvent introduced into spandex during the production process causes pores in the fiber. These pores will form holes in the fiber structure, affecting the density and continuity of the fiber. When external force is applied, the pores will produce stress concentration, making the fiber structure uneven, causing discontinuous load transfer, making the fiber easy to break or deform, thereby weakening the elastic performance of the fiber. Summary of the invention
[0003] The purpose of the present invention is to provide a highly elastic and wrinkle-proof fabric and a preparation method thereof. The present invention discloses a highly elastic and wrinkle-proof fabric and a preparation method thereof, and belongs to the technical field of textile fabric preparation. The method comprises the following steps: a chain extender, a compounding agent, a polyol and a diisocyanate are synthesized into a polyurethane resin in a twin-screw extruder in one step, crushed, dissolved, and a polyurethane solution is obtained; the polyurethane solution, a sodium hydroxide solution, bromine gas, and aluminum chloride are added to a reactor for heating and reacting for 4-8 hours, benzene is added to the reactor, the temperature is lowered to 0-5°C and reacted for 15-20 hours, a finishing agent is added, stirred, separated, and an organic phase A is taken to obtain a mixed solution; the mixed solution is subjected to electrostatic spinning, stretched and cured to obtain a highly elastic and wrinkle-proof fabric; the benzene ring is connected to the urea functional group of the hard segment through a chemical bond, the sliding and relative displacement of the fiber hard segment are reduced, the node firmness of the hard segment is improved, and the fiber elasticity is improved, and the benzene ring is introduced to increase the fiber thickness and improve its wrinkle resistance.
[0004] The technical problem to be solved by the present invention is to provide a method for preparing a high-elastic wrinkle-resistant fabric to enhance the elastic properties of the fiber.
[0005] The purpose of the present invention can be achieved through the following technical solutions:
[0006] A highly elastic and wrinkle-resistant fabric and a preparation method thereof, comprising the following steps:
[0007] (1) synthesizing a polyurethane resin in one step by a chain extender, a compounding agent, a polyol and a diisocyanate in a twin-screw extruder, crushing and dissolving the polyurethane resin to obtain a polyurethane solution;
[0008] (2) adding the polyurethane solution, sodium hydroxide solution, bromine gas and aluminum chloride into a reaction kettle and heating for reaction for 4-8 hours, adding benzene into the reaction kettle, cooling to 0-5° C. and reacting for 15-20 hours, adding a finishing agent, stirring, separating, and taking an organic phase A to obtain a mixed solution;
[0009] (3) The mixed solution is subjected to electrostatic spinning, and stretched and solidified to obtain the highly elastic and wrinkle-resistant fabric.
[0010] As a preferred technical solution of the present invention, in step (1), the mass ratio of the chain extender, the complexing agent, the polyol and the diisocyanate is 1:0.05-0.1:3-4:5-6.
[0011] As a preferred technical solution of the present invention, in step (2), the mass ratio of the polyurethane solution, sodium hydroxide solution, bromine gas, aluminum chloride, benzene and finishing agent is 1:1-2:2-3:1.2-1.8:1-1.2:0.2-0.5.
[0012] As a preferred technical solution of the present invention, the preparation of the chain extender comprises the following steps:
[0013] Mix carbon tetrachloride, phosphorus oxychloride and hydrochloric acid, heat to 25°C in a water bath, add butanetetraol while stirring, keep the temperature at 25°C for 1-1.5h, raise the temperature to 50°C and continue the reaction for 5-6h, lower the temperature to 30°C and stir for 3-5h, extract to obtain organic phase B, add the organic phase B to sodium hydroxide solution, separate, and take organic phase C to obtain the chain extender.
[0014] As a preferred technical solution of the present invention, the mass ratio of carbon tetrachloride, phosphorus oxychloride, hydrochloric acid, butanetetraol and sodium hydroxide solution is 10-15:1:0.5-1:3-4:6-8.
[0015] As a preferred technical solution of the present invention, the preparation of the finishing agent comprises the following steps:
[0016] The finishing agent is obtained by mixing chitosan, benzophenone imine and linoleic acid, heating and stirring, cooling and filtering.
[0017] As a preferred technical solution of the present invention, the mass ratio of chitosan, benzophenone imine and linoleic acid is 1:0.13-0.2:0.53-0.6;
[0018] The heating and stirring refers to heating and stirring in a water bath at 80°C for 4-6 hours; the cooling refers to cooling to 25°C.
[0019] As a preferred technical solution of the present invention, the compounding agent is at least one of phenol, p-phenylenediamine and benzophenone.
[0020] As a preferred technical solution of the present invention, the aspect ratio of the screw of the twin-screw extruder is 30-45:1, the extrusion temperature is 165-240°C, the screw speed is 150-200r / min, and the head pressure is 100-150kg / cm 2 .
[0021] A highly elastic and wrinkle-resistant fabric prepared by the above-mentioned preparation method.
[0022] Beneficial effects of the present invention:
[0023] (1) The present invention discloses a highly elastic and wrinkle-resistant fabric and a preparation method thereof. After the polyurethane is polymerized, a benzene ring is introduced to form a stable chemical bond connection with the urea functional group of the hard segment through nucleophilic substitution, thereby improving the compactness of the hard segment and increasing the firmness of the node of the hard segment, effectively hindering the sliding and relative displacement of the fiber hard segment, thereby improving the elasticity of the fabric, and introducing a benzene ring to increase the fiber thickness and improve its wrinkle resistance.
[0024] (2) Furthermore, during the fabric preparation process, a stable π-π stacking is formed between the chitosan in the finishing agent and the benzene ring, thereby adsorbing each other and filling the finishing agent into the pores generated by the fibers; at the same time, chitosan is mixed with benzophenone imine and linoleic acid, benzophenone imine improves the dispersibility of chitosan in linoleic acid, and linoleic acid serves as a carrier for the flow of chitosan, so that chitosan can more evenly fill the gaps in the polyurethane fibers. Chitosan contains a large number of hydroxyl and amino groups, which adsorb each other with the urea group to improve the pore filling rate. After the gaps between the fibers are filled, when the fibers are subjected to external stress in the gaps, the finishing agent will bear part of the stress, thereby reducing the relative displacement of the fiber hard segments, increasing the compactness of the fiber hard segments, and reducing the wrinkle problem of the fibers.
[0025] (3) Furthermore, the introduction of hydroxyl-rich chain extenders during the polyurethane synthesis process can improve the mechanical properties of polyurethane and the viscosity of the polyurethane system, which is beneficial to adjusting the processing properties of the fabric.
[0026] (4) Furthermore, in the process of introducing benzene rings, in order to prevent the polyurethane structure from being corroded by alkali solution, a phosphoric acid group is introduced into the chain extender to improve the alkali resistance of the polyurethane, which can effectively reduce the corrosive effect of alkali solution on the polyurethane structure, thereby improving the performance of the polyurethane. DETAILED DESCRIPTION
[0027] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments.
[0028] Example 1
[0029] 10 parts by mass of carbon tetrachloride, 1 part by mass of phosphorus oxychloride and 0.5 parts by mass of hydrochloric acid were mixed, heated to 25°C in a water bath, 3 parts by mass of butanetetrol were added while stirring, the mixture was kept at 25°C for 1 hour, the mixture was heated to 50°C for further reaction for 5 hours, the mixture was cooled to 30°C and stirred for 3 hours, and an organic phase B was obtained by extraction. The organic phase B was added to 6 parts by mass of a sodium hydroxide solution with a concentration of 2 mol / L, and the mixture was separated. An organic phase C was obtained to obtain the chain extender. The concentration of the hydrochloric acid was 2 mol / L.
[0030] 1 part by mass of chitosan, 0.13 part by mass of benzophenone imine and 0.53 part by mass of linoleic acid were mixed, heated and stirred in a water bath at 80° C. for 4 hours, then cooled to 25° C., and filtered to obtain the finishing agent;
[0031] 1 part by mass of chain extender, 0.05 part by mass of phenol, 3 parts by mass of glycerol and 5 parts by mass of diisocyanate were placed in a twin-screw extruder with an aspect ratio of 30:1 at an extrusion temperature of 165°C, a screw speed of 150 r / min and a die pressure of 100 kg / cm 2 The polyurethane resin is synthesized under the conditions of the first step, crushed, and dissolved with 10 parts by mass of acetone to obtain a polyurethane solution; 1 part by mass of the polyurethane solution, 1 part by mass of a 40% sodium hydroxide solution, 2 parts by mass of bromine gas, and 1.2 parts by mass of aluminum chloride are added to a reactor and heated at 45°C for reaction for 4 hours, 1 part by mass of benzene is added to the reactor, the temperature is lowered to 0°C for reaction for 15 hours, 0.2 parts by mass of a finishing agent is added, stirred, separated, and an organic phase A is taken to obtain a mixed solution; the mixed solution is electrostatically spun at a voltage of 50 kV, stretched and cured to obtain the highly elastic and wrinkle-resistant fabric.
[0032] Example 2
[0033] 12 parts by mass of carbon tetrachloride, 1 part by mass of phosphorus oxychloride and 0.7 parts by mass of hydrochloric acid were mixed, heated to 25°C in a water bath, 3.5 parts by mass of butanetetrol were added while stirring, the mixture was kept at 25°C for 1.25h, the mixture was heated to 50°C for further reaction for 5.5h, the mixture was cooled to 30°C and stirred for 4h, and an organic phase B was obtained by extraction. The organic phase B was added to 7 parts by mass of a sodium hydroxide solution with a concentration of 2mol / L, and the mixture was separated, and an organic phase C was taken to obtain the chain extender; the concentration of the hydrochloric acid was 2mol / L;
[0034] 1 part by mass of chitosan, 0.17 part by mass of benzophenone imine and 0.57 part by mass of linoleic acid were mixed, heated and stirred in a water bath at 80° C. for 5 h, then cooled to 25° C., and filtered to obtain the finishing agent;
[0035] 1 part by mass of chain extender, 0.07 part by mass of p-phenylenediamine, 3.5 parts by mass of xylitol and 5.5 parts by mass of diisocyanate were placed in a twin-screw extruder with an aspect ratio of 40:1 at an extrusion temperature of 200°C, a screw speed of 180 r / min, and a die pressure of 120 kg / cm 2 The polyurethane resin is synthesized under the conditions of the first step, crushed, and dissolved with 10 parts by mass of acetone to obtain a polyurethane solution; 1 part by mass of the polyurethane solution, 1.5 parts by mass of a 40% sodium hydroxide solution, 2.5 parts by mass of bromine gas, and 1.6 parts by mass of aluminum chloride are added to a reactor and heated at 42°C for reaction for 5 hours, 1.1 parts by mass of benzene are added to the reactor, the temperature is lowered to 2.5°C for reaction for 17 hours, 0.3 parts by mass of a finishing agent are added, stirred, separated, and an organic phase A is taken to obtain a mixed solution; the mixed solution is electrostatically spun at a voltage of 50 kV, stretched and cured to obtain the highly elastic and wrinkle-resistant fabric.
[0036] Example 3
[0037] 15 parts by mass of carbon tetrachloride, 1 part by mass of phosphorus oxychloride and 1 part by mass of hydrochloric acid were mixed, heated to 25°C in a water bath, 4 parts by mass of butanetetrol were added while stirring, the mixture was kept at 25°C for 1.5 hours, the mixture was heated to 50°C for further reaction for 6 hours, the mixture was cooled to 30°C and stirred for 5 hours, and the mixture was extracted to obtain an organic phase B, the organic phase B was added to 8 parts by mass of a sodium hydroxide solution having a concentration of 2 mol / L, the mixture was separated, and an organic phase C was taken to obtain the chain extender; the concentration of the hydrochloric acid was 2 mol / L;
[0038] 1 part by mass of chitosan, 0.2 part by mass of benzophenone imine and 0.6 part by mass of linoleic acid were mixed, heated and stirred in a water bath at 80° C. for 6 hours, then cooled to 25° C., and filtered to obtain the finishing agent;
[0039] 1 part by mass of chain extender, 0.1 part by mass of benzophenone, 4 parts by mass of sorbitol and 6 parts by mass of diisocyanate were placed in a twin-screw extruder with an aspect ratio of 45:1 at an extrusion temperature of 240°C, a screw speed of 200 r / min, and a die pressure of 150 kg / cm 2 The polyurethane resin is synthesized under the conditions of the first step, crushed, and dissolved with 10 parts by mass of acetone to obtain a polyurethane solution; 1 part by mass of the polyurethane solution, 2 parts by mass of a 40% sodium hydroxide solution, 3 parts by mass of bromine gas, and 1.8 parts by mass of aluminum chloride are added to a reactor and heated at 40°C for reaction for 8 hours, 1.2 parts by mass of benzene are added to the reactor, the temperature is lowered to 5°C for reaction for 20 hours, 0.5 parts by mass of a finishing agent are added, stirred, separated, and an organic phase A is taken to obtain a mixed solution; the mixed solution is electrostatically spun at a voltage of 50 kV, stretched and cured to obtain the highly elastic and wrinkle-resistant fabric.
[0040] Comparative Example 1
[0041] 1 part by mass of chitosan, 0.17 part by mass of benzophenone imine and 0.57 part by mass of linoleic acid were mixed, heated and stirred in a water bath at 80° C. for 5 h, then cooled to 25° C., and filtered to obtain the finishing agent;
[0042] 1 part by mass of 1,4-butanediol, 0.07 part by mass of p-phenylenediamine, 3.5 parts by mass of xylitol and 5.5 parts by mass of diisocyanate were placed in a twin-screw extruder with an aspect ratio of 40:1 at an extrusion temperature of 200°C, a screw speed of 180 r / min, and a die pressure of 120 kg / cm 2 The polyurethane resin is synthesized under the conditions of the first step, crushed, and dissolved with 10 parts by mass of acetone to obtain a polyurethane solution; 1 part by mass of the polyurethane solution, 1.5 parts by mass of a 40% sodium hydroxide solution, 2.5 parts by mass of bromine gas, and 1.6 parts by mass of aluminum chloride are added to a reactor and heated at 42°C for reaction for 5 hours, 1.1 parts by mass of benzene are added to the reactor, the temperature is lowered to 2.5°C for reaction for 17 hours, 0.3 parts by mass of a finishing agent are added, stirred, separated, and an organic phase A is taken to obtain a mixed solution; the mixed solution is electrostatically spun at a voltage of 50 kV, stretched and cured to obtain the highly elastic and wrinkle-resistant fabric.
[0043] Comparative Example 2
[0044] 12 parts by mass of carbon tetrachloride, 1 part by mass of phosphorus oxychloride and 0.7 parts by mass of hydrochloric acid were mixed, heated to 25°C in a water bath, 3.5 parts by mass of butanetetrol were added while stirring, the mixture was kept at 25°C for 1.25h, the mixture was heated to 50°C for further reaction for 5.5h, the mixture was cooled to 30°C and stirred for 4h, and an organic phase B was obtained by extraction. The organic phase B was added to 7 parts by mass of a sodium hydroxide solution with a concentration of 2mol / L, and the mixture was separated, and an organic phase C was taken to obtain the chain extender; the concentration of the hydrochloric acid was 2mol / L;
[0045] 1 part by mass of chain extender, 0.07 part by mass of p-phenylenediamine, 3.5 parts by mass of xylitol and 5.5 parts by mass of diisocyanate were placed in a twin-screw extruder with an aspect ratio of 40:1 at an extrusion temperature of 200°C, a screw speed of 180 r / min, and a die pressure of 120 kg / cm 2 The polyurethane resin is synthesized under the conditions of the first step, crushed, and dissolved with 10 parts by mass of acetone to obtain a polyurethane solution; 1 part by mass of the polyurethane solution, 1.5 parts by mass of a 40% sodium hydroxide solution, 2.5 parts by mass of bromine gas, and 1.6 parts by mass of aluminum chloride are added to a reactor and heated at 42°C for reaction for 5 hours, 1.1 parts by mass of benzene is added to the reactor, the temperature is lowered to 2.5°C for reaction for 17 hours, separated, and the organic phase A is taken to obtain a mixed solution; the mixed solution is electrostatically spun at a voltage of 50 kV, stretched and cured to obtain the highly elastic and wrinkle-resistant fabric.
[0046] Comparative Example 3
[0047] 12 parts by mass of carbon tetrachloride, 1 part by mass of phosphorus oxychloride and 0.7 parts by mass of hydrochloric acid were mixed, heated to 25°C in a water bath, 3.5 parts by mass of butanetetrol were added while stirring, the mixture was kept at 25°C for 1.25h, the mixture was heated to 50°C for further reaction for 5.5h, the mixture was cooled to 30°C and stirred for 4h, and an organic phase B was obtained by extraction. The organic phase B was added to 7 parts by mass of a sodium hydroxide solution with a concentration of 2mol / L, and the mixture was separated, and an organic phase C was taken to obtain the chain extender; the concentration of the hydrochloric acid was 2mol / L;
[0048] 1 part by mass of chitosan, 0.17 part by mass of benzophenone imine and 0.57 part by mass of linoleic acid were mixed, heated and stirred in a water bath at 80° C. for 5 h, then cooled to 25° C., and filtered to obtain the finishing agent;
[0049] 1 part by mass of chain extender, 0.07 part by mass of p-phenylenediamine, 3.5 parts by mass of xylitol and 5.5 parts by mass of diisocyanate were placed in a twin-screw extruder with an aspect ratio of 40:1 at an extrusion temperature of 200°C, a screw speed of 180 r / min, and a die pressure of 120 kg / cm 2 The polyurethane resin is synthesized under the conditions of the first step, crushed, and dissolved with 10 parts by mass of acetone to obtain a polyurethane solution; 1 part by mass of the polyurethane solution is added to a reactor, 0.3 parts by mass of a finishing agent is added, stirred, separated, and an organic phase A is taken to obtain a mixed solution; the mixed solution is electrostatically spun at a voltage of 50 kV, stretched and cured to obtain the highly elastic and wrinkle-resistant fabric.
[0050] Performance Testing
[0051] Anti-wrinkle performance test was carried out according to GB / T 3819-1997;
[0052] The elasticity test was carried out according to ASTM D 3107-75.
[0053] The high-elastic wrinkle-resistant fabrics prepared in Examples 1-3 and Comparative Examples 1-3 were tested for wrinkle resistance and elasticity according to the above standards. The test results are shown in Table 1 below:
[0054] Table 1
[0055]
[0056]
[0057] It can be seen from Table 1 that comparative examples 1-3 are prepared on the basis of example 2, wherein the anti-wrinkle performance of comparative examples 1 and 3 is reduced, and the anti-wrinkle performance of comparative example 2 is significantly reduced; the elasticity of comparative examples 1 and 3 is worse than that of example 2, and comparative example 3 is worse than comparative example 1.
[0058] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A method for preparing a highly elastic and wrinkle-resistant fabric, characterized in that: The following steps are involved: (1) synthesizing a polyurethane resin in one step by a chain extender, a compounding agent, a polyol and a diisocyanate in a twin-screw extruder, crushing and dissolving the polyurethane resin to obtain a polyurethane solution; (2) adding the polyurethane solution, sodium hydroxide solution, bromine gas and aluminum chloride into a reaction kettle and heating for reaction for 4-8 hours, adding benzene into the reaction kettle, cooling to 0-5° C. and reacting for 15-20 hours, adding a finishing agent, stirring, separating, and taking an organic phase A to obtain a mixed solution; (3) The mixed solution is subjected to electrostatic spinning, and stretched and solidified to obtain the highly elastic and wrinkle-resistant fabric.
2. The method for preparing a highly elastic and wrinkle-resistant fabric according to claim 1, characterized in that: In step (1), the mass ratio of the chain extender, the complexing agent, the polyol and the diisocyanate is 1:0.05-0.1:3-4:5-6.
3. The method for preparing a highly elastic and wrinkle-resistant fabric according to claim 1, characterized in that: In step (2), the mass ratio of the polyurethane solution, the sodium hydroxide solution, the bromine gas, the aluminum chloride, the benzene and the finishing agent is 1:1-2:2-3:1.2-1.8:1-1.2:0.2-0.
5.
4. The method for preparing a highly elastic and wrinkle-resistant fabric according to claim 1, characterized in that: The preparation of the chain extender comprises the following steps: Mix carbon tetrachloride, phosphorus oxychloride and hydrochloric acid, heat to 25°C in a water bath, add butanetetraol while stirring, keep the temperature at 25°C for 1-1.5h, raise the temperature to 50°C and continue the reaction for 5-6h, lower the temperature to 30°C and stir for 3-5h, extract to obtain organic phase B, add the organic phase B to sodium hydroxide solution, separate, and take organic phase C to obtain the chain extender.
5. The method for preparing a highly elastic and wrinkle-resistant fabric according to claim 4, characterized in that: The mass ratio of the carbon tetrachloride, phosphorus oxychloride, hydrochloric acid, butanetetraol and sodium hydroxide solution is 10-15:1:0.5-1:3-4:6-8.
6. The method for preparing a highly elastic and wrinkle-resistant fabric according to claim 1, characterized in that: The preparation of the finishing agent comprises the following steps: The finishing agent is obtained by mixing chitosan, benzophenone imine and linoleic acid, heating and stirring, cooling and filtering.
7. The method for preparing a highly elastic and wrinkle-resistant fabric according to claim 6, characterized in that: The mass ratio of chitosan, benzophenone imine and linoleic acid is 1:0.13-0.2:0.53-0.6; The heating and stirring refers to heating and stirring in a water bath at 80°C for 4-6 hours; the cooling refers to cooling to 25°C.
8. The method for preparing a highly elastic and wrinkle-resistant fabric according to claim 1, characterized in that: The compounding agent is at least one of phenol, p-phenylenediamine and benzophenone.
9. The method for preparing a highly elastic and wrinkle-resistant fabric according to claim 1, characterized in that: The aspect ratio of the screw of the twin-screw extruder is 30-45:1, the extrusion temperature is 165-240°C, the screw speed is 150-200r / min, and the die pressure is 100-150kg / cm 2 .
10. A highly elastic and wrinkle-resistant fabric prepared by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Preparation of chitosan-polyurethane ion complex elastomer material
CN101497698A
Chiral 5,5,10,10-tetraaryl-bicyclo[4.4.0]-3,8-bisphosphate and preparation method and application thereof
CN105541918A
Natural polymer modified polyurethane and preparation method thereof
CN112011025A
Polyurethane elastic yarn, and method for producing the same
JP2010121240A